Green assessment and improvement framework for electric bus operational system - Teo, Lay Eng; Goh, Siew Yoke; Khoo, Hooi Ling (Penerbit Universiti Kebangsaan Malaysia, 2021)
In response to the worldwide environmental problem and fossil oil dependency concern, electric bus (EB) has emerged as a promising green transport to alleviate air pollution. However, there is no available method on how to quantify the environmental (green) performance of EB operational system that could provide proper guidance to the bus operators. Thus, this study aims to develop a green assessment and improvement framework for EB operational system which is capable of capturing bus noise, emission, and energy consumption level explicitly in quantifying the respective green index. To do this, the approaches of Gini Index, Analytic Hierarchy as well as Weighted-grading are employed accordingly. The resultant Green Performance Index (GPI) is vital not only to enhance the green performance of EB operational system, but also to tackle the needs and preferences of the bus operators in meeting the demand of passengers. By analysing a study area in Putrajaya (Malaysia), the findings show that the green performance of EB operational system would vary across numerous operational factors, including load factor, bus frequency, and bus type. The results also highlight that the green weightage of energy consumption emerges with the highest value (approximately 69%). Besides that, it was found that the improvement strategy of load factor increment is beneficial to improve the GPI of the bus operator, up to 37.9%. Concisely, it is anticipated that the developed approach as well as the resultant findings would yield useful insights especially to the bus operators to operate EB in a greener and better manner.